2016
DOI: 10.1021/acs.molpharmaceut.6b00033
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Matrix Metalloproteinase-9 of Proliferating Smooth Muscle Cells as a Trigger for Drug Release from Stent Surface Polymers in Coronary Arteries

Abstract: Cardiovascular diseases are the leading causes of death in industrialized countries. Atherosclerotic coronary arteries are commonly treated with percutaneous transluminal coronary intervention followed by stent deployment. This treatment has significantly improved the clinical outcome. However, triggered vascular smooth muscle cell (SMC) proliferation leads to in-stent restenosis in bare metal stents. In addition, stent thrombosis is a severe side effect of drug eluting stents due to inhibition of endotheliali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…36 However, we chose this molecule due to its high lipophilicity and the possibility to form an amphiphilic prodrug, when linking to a hydrophilic moiety. The particular peptide (NH 2 -Ahx-SRLSLPGC-COOH) used in the synthesis of PH8 was previously investigated for MMP9 triggered release of paclitaxel from stent surfaces by Gliesche et al 37 and from polymersomes by Porta et al 38 The cleavage of this peptide by MMP9 was verified in a cell-free assay and reflected the herein measured MMP9 content in the supernatant of cultured LN-18, U87 MG, and A549 cells. Inhibition of the enzymatic activity by addition of the MMP9 inhibitor revealed the contribution of MMP9 to the release.…”
Section: ■ Discussionsupporting
confidence: 56%
“…36 However, we chose this molecule due to its high lipophilicity and the possibility to form an amphiphilic prodrug, when linking to a hydrophilic moiety. The particular peptide (NH 2 -Ahx-SRLSLPGC-COOH) used in the synthesis of PH8 was previously investigated for MMP9 triggered release of paclitaxel from stent surfaces by Gliesche et al 37 and from polymersomes by Porta et al 38 The cleavage of this peptide by MMP9 was verified in a cell-free assay and reflected the herein measured MMP9 content in the supernatant of cultured LN-18, U87 MG, and A549 cells. Inhibition of the enzymatic activity by addition of the MMP9 inhibitor revealed the contribution of MMP9 to the release.…”
Section: ■ Discussionsupporting
confidence: 56%
“…However, comparing the applicability of the above-mentioned peptides (AVR and SRL) in primary human coronary artery muscle cells, we observed that in this cellular system, where only MMP-9 activity was detected, the SRL-peptide was much more likely cleaved, releasing paclitaxel from a modified surface, than if the AVR peptide was used as the linker. Our finding suggested that there is a higher affinity of MMP-9 toward the SRL-peptide …”
Section: Discussionmentioning
confidence: 58%
“…toward the SRL-peptide. 51 In general, the diameter of rigid spherical polymersomes should be between 120 and 200 nm to prevent clearance in capillary beds or lymph nodes, splenic filtration, and entrapment in the space of Disse and hepatic parenchyma. 52 Assessing the hydrodynamic diameter of the unloaded polymersomes suggested no significant change in the average 48 However, the size distribution was significantly changed after loading with paclitaxel, and the surface crosslinking of loaded polymersomes even resulted in a loss of the Gaussian distribution, as determined by DLS.…”
Section: Molecular Pharmaceuticsmentioning
confidence: 99%
“…This fibrous system was designed for potential applications in coronary stents [122]. Drug loaded PLLA has also been conjugated with the two ends of the matrix metalloproteinase-9 (MMP-9) for a selective drug release, beneficial for stent endothelialization, thereby decreasing the risk of restenosis and thrombosis [123]. Tyrosine kinase inhibitor (ST638) was encapsulated onto prototype Igaki-Tamai stents and implanted in porcine coronary arteries.…”
Section: Stentsmentioning
confidence: 99%